A Unique Case of Pneumatised Styloid Process with Cholesteatoma - Mostayn Alam; Raghav C. Dwivedi; Faruque Riffat; Daniel Scoffings; David Moffat; Piyush Jani (Case Reports in Otolaryngology)
Pneumatisation of styloid process is a very rare finding and has never been reported previously. We present a unique case of a pneumatised styloid process with a cholesteatoma arising within the cavity. We describe the clinical features, associated radiological findings, and management of this lesion.